Effect of certain additives on the freezability of crossbred bull semen - SRIVASTAVA, SUSHANT; KUMAR, S (The Indian Journal of Animal Reproduction, 2023)
Thirty two ejaculates (8 each from FH and FxH bulls) were subjected to freezing. Cervical mucus penetration test andhypo-osmotic swelling test used for quality assessment of fresh and frozen thawed spermatozoa. Sperm penetration distance (SPD) travelled by vanguard spermatozoa of HF and FxH bulls were 45.06 ± 3.32 and 39.94 ± 2.98mm of fresh semen and 19.69± 0.47 and 18.38 ± 0.59mm of fresh semen in 60 min. SPD traveled by vanguard spermatozoa differed significantly (P
Keywords: Semen; freezing; additives; penetration distance; motility; hypo-osmotic response